Crustose coralline algae and biodiversity enhancement: The role of Lithophyllum stictiforme in structuring Mediterranean coralligenous reefs. (5th November 2022) - Piazzi, L.; Pinna, F.; Ceccherelli, G.
Abstract: Biogenic structures edified by crustose coralline algae (CCA) are known to enhance biodiversity, but the mechanisms involved are only partially defined. This study aims at contributing to the knowledge of the interaction between habitat-builder CCA and epibiont assemblages through a manipulative approach. To achieve this objective, transplantations of the CCA Lithophyllum stictiforme were performed to test the following hypotheses: 1) the structure of L. stictiforme epibiont assemblage changes between depth and biogeographic area; 2) L. stictiforme epibiont assemblage is different and more diversified than the assemblage recruited on bare rock; 3) the early L. stictiforme epibiont assemblage differ from the mature L. stictiforme epibiont assemblage. A total of 63 epibiontic taxa were found on the transplanted L. stictiforme thalli, such as 7 Chlorophyta, 10 Ochrophyta, 40 Rhodophyta, 1 Sarcomastigophora, 1 Porifera, 4 Bryozoa. The sessile assemblage recruited on transplanted L. stictiforme thalli depended on sites and depths, and it had a higher taxa richness compared to that colonizing the bare rock. The early recruited assemblage on L. stictiforme transplanted thalli compared to the mature assemblage on untouched thalli was different mostly in the relative abundance of taxa, rather than in species composition. These manipulative experiments highlighted for the first time the role of a common CCA on the development and biodiversity of coralligenous assemblages, contributing to emphasize the importance of CCA conservation efforts. Highlights: Lithophyllum stictiforme thalli were transplanted at different depths and sites. The interaction between crustose coralline algae and epibionts was investigated. The assemblages had a higher diversity on transplanted thalli than on bare rock.